Penyelesaian Sengketa Pilkada Serentak 2015 dalam Perspektif Electoral Justice System - Bambang Eka Cahya Widodo (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2016)
Electoral disputes interpreted as a complaint, protests, claims, cancellations, and contestation in the electoral process related. In the implementation of the elections including the concurrently local election 2015 disputes is necessary thing happened. In the perspective of electoral justice system, dispute resolution must meet the elements such the right to a settlement of electoral disputes; the election standard devices and procedures are clearly defined; the electoral dispute resolution body who have the knowledge and impartiality; the judicial systems that facilitate the achievement of the decision; the existence of clear regulations concerning the burden of proof and standard of submission of evidence clearly defined; the effective settlement system and meaningful and the effective of stakeholders education. This article intended to examine and assess whether the electoral dispute resolution system that is prepared for concurrent local election is adequate or not in the perspective of electoral justice system. Method used is by analyzing 2015 concurrent election legal framework and institutional framework for organizing and analyzing the elements of the institutional framework of the institutions involved in the resolution of electoral disputes in the concurrent election of 2015. In addition, the analysis was also directed at other aspects in the resolution of electoral disputes such as the availability of prevention system (preventive system) and alternative dispute resolution system that can be used in the concurrently election dispute resolution 2015. The analysis also uses actual cases that develop during the stages of the concurrent elections for comparison purposes in the implementation of regulations disputed election, as well as to examine the capacity and capability of the electoral dispute resolution body that are responsible for the settlement of electoral disputes.